2000
DOI: 10.1093/nar/28.2.593
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transition in DNA on a cold surface

Abstract: The contour length of DNA fragments, deposited and imaged on mica under buffer, was measured as a function of deposition temperature. Extended DNA molecules (on Ni-and silane-treated surfaces) contract rapidly with falling temperature, approaching the contour length of A-DNA at 2°°°°C. The contraction is not unique to a specific sequence and does not occur in solution at 2°°°°C or on a surface at 25°°°°C, indicating that it arises from a combination of low temperature and surface contact. It is probably a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The Co(phen) 3 3 + consisted of three vertical tris(1,10‐phenanthroline) and one Co 2+ ion, and could associate with the DNA by groove binding (Coury et al , 1997). The association of a few Co(phen) 3 3 + with DNA molecules did not alter the conformation of DNA but enhanced the adsorption of DNA on the mica surface (Feng et al , 2000). However, the association of a large number of Co(phen) 3 3 + molecules with DNA condensed the DNA molecules, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Co(phen) 3 3 + consisted of three vertical tris(1,10‐phenanthroline) and one Co 2+ ion, and could associate with the DNA by groove binding (Coury et al , 1997). The association of a few Co(phen) 3 3 + with DNA molecules did not alter the conformation of DNA but enhanced the adsorption of DNA on the mica surface (Feng et al , 2000). However, the association of a large number of Co(phen) 3 3 + molecules with DNA condensed the DNA molecules, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the emphases of these theoretical studies were only focussed on the structure of molecules on a surface, and the relationship of the molecules on a surface and in a solution. Actually, the surface could not only alter the conformations of molecules in a solution but also affect the interaction between DNA and protein or small molecules, even if the complex was disassembled (Feng et al , 2000; Nagami et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The various conformations of DNA (Lyubchenko and Shlyakhtenko, 1997;Oussatcheva et al, 2004;Zheng et al, 2002), conformational changes (Bussiek et al, 2003;Feng et al, 2000) as well as their complexes with other molecules (Dame et al, 2000;Lysetska et al, 2002;Tseng et al, 2005) have been imaged by AFM on a mica surface or a functionalized mica surface. It is also important to image DNA binding to a gold surface or a functionalized gold surface so that in future the effect of an applied electric field on the DNA surface conformation can be studied (Wackerbarth et al, 2004), since gold surfaces or functionalized gold surfaces have been extensively employed to construct DNA microchips.…”
Section: Introductionmentioning
confidence: 99%
“…13 Imaging with these methods also generally requires mounting the sample on a surface, which likely alters the conformation of the DNA and its attached particles. 20 For sampling in solution, direct imaging is not usually feasible, but dimensional characterization is still achievable using spectroscopy and, in particular, by monitoring Förster resonance energy transfer (FRET) between chromophores attached to the DNA. Many studies of DNA utilizing FRET have been reported in the literature, although typically it is used in a stand-alone mode as a spatial characterization method.…”
mentioning
confidence: 99%